Determinants of Consumer Intention to Adopt Digital Payment in Culinary MSMEs - Elisa Daniati Edison; Mira Aprila; Nur Azizah (Trunojoyo University of Madura, 2026)
The growing development of digital payment platforms has transformed the way consumers conduct transactions and has further accelerated the digital transformation of MSMEs. Although QRIS has been widely adopted across Indonesia, empirical evidence regarding the psychological factors that shape consumers’ intentions to utilize this payment method, particularly within the culinary MSME sector, remains limited. This research investigates the effects of perceived usefulness and perceived ease of use on consumers’ intention to adopt QRIS, while also assessing the mediating role of attitude in this association. The study involved 150 respondents who had previously used QRIS when making transactions at culinary MSMEs in Padang, Indonesia. Using a quantitative research design, the proposed model was analyzed through PLS-SEM. The results demonstrate that perceptions of usefulness and ease of operation both play a significant role in shaping positive attitudes toward QRIS usage. Perceived ease of use emerged as the strongest antecedent of attitude. In addition, attitude was found to significantly influence behavioral intention, suggesting that positive evaluations of QRIS play an important role in encouraging future usage. Perceived usefulness directly enhances consumers’ intention to use QRIS; however, the influence of perceived ease of use on behavioral intention was not found to be statistically significant. Further analysis reveals that attitude fully mediates the association between perceived ease of use and behavioral intention and partially mediates the linkage between perceived usefulness and behavioral intention. These findings suggest that consumers’ adoption decisions are not solely driven by functional benefits or technological simplicity but are largely influenced by the positive attitudes developed through their interaction with the payment system. This study enriches the digital payment and technology adoption literature by demonstrating the importance of attitudinal mechanisms in explaining QRIS adoption behavior within developing country MSME contexts.